Development and Evaluation of SENSE-ational Mealtimes: a Book for Families with Mealtime Difficulties - Stapleton, Denise; Griffiths, G.; Sherriff, Jillian (Routledge, 2013)
Many families with young children experience mealtime difficulties whereby the child eats a limited range of foods and/or refuses new food. Clinical interventions typically include behaviour training, enhancement of parenting skills and nutrition education. Clinical experience and a review of the literature across several domains suggested that interventions that optimise reflective functioning and understandings about sensory preferences at mealtimes are needed for both mild and complex mealtime difficulties. This study describes the development of the SENSE-ational Mealtimes book for families with mealtime difficulties and reports the findings of the initial evaluation. A questionnaire was used to assess the change in the frequency of difficult mealtimes, level of concern, understandings, feelings and goals of mothers 2 months after the book was distributed in a community setting. Mothers also provided feedback regarding helpfulness of the book, needs of families and recommendations. There was a statistically significant improvement in all aspects, namely frequency of mealtime difficulties, level of concern, understandings, feelings and goals. The subjective data indicated that the concepts instrumental in enhancing most mothers' understandings were how sensory preferences and past experiences of all members of the family had an impact on mealtime interactions. Initial evaluation suggests that wide-spread access to the SENSE-ational Mealtimes book could be an inexpensive approach to reduce the costs of adverse effects of mealtime difficulties on the emotional well-being of families and dietary intake of children. Mothers unanimously recommended the SENSE-ational Mealtimes book for both targeted prevention of and early intervention with mealtime difficulties in families.